Model Pendekatan Nilai Konstanta Penggorengan Vakum Keripik Pepaya - R Sugiharto (Jurusan Teknologi Pertanian, 2013)
This research is purposed to examine constant analysis model with two dependent variables, they are vacuum pressure (-p) within three levels: 60; 65 and 70 cmHg and frying temperature (T) in three levels: 70; 80; and 90oC with the ratio product mass toward medium mass (oil) R=1:20 within twice repetition for papaya chips frying. Analysis is conducted to the result of research toward the influence of each treatment with statistic experiment LSD (Least Square Design) with vacuum frying constant (K). Research with analysis model approach prefer on emphasizing functional relation between dependent variable and independent variable within nonlinear equation of logarithmic exponential with vacuum pressure (-p) as the independent variable andÂ medium temperature or frying oil (T) in three level like have been mentioned.The analysis result with two independent variables vacuum pressure (-p) and vacuum frying temperature (T) got an equation for constant value of vacuum frying (KP=minut-1) and the prediction is: KP=1.4642*exp(-0.5*((((-p)-181.838)/45.1584)^2+((T-93.7826)/26.006)^2)); R2=0.921 The implementation of analysis result of vacuum frying constant value (K) which is used to predict history of chips water/moist level along the process of vacuum frying show the average of reliable validation experiment result (R2>0.94). Then the experiment result of fried chips very related to the timing of frying that have been applied, with relative of final water level which not truly different in the test level 5%.Â Keywords: vacuum frying, frying constanta and papaya chips.